A Formative Evaluation of a Master's‐Level Career‐Coaching Course for Performance Improvement Students. Issue 4 (16th April 2019) - Villachica, Steven W.; Stieha, Vicki; Giacumo, Lisa; Becker, Lesa; Fenner, Jo Ann
Abstract : The authors conducted a formative evaluation of an iteratively evolving career‐coaching course. All 11 master's students who had enrolled in the course between Winter 2016 and Fall 2017 participated in the evaluation. Our evaluation addressed three research questions: (1) To what extent does participation in the career‐coaching course affect participant confidence? (2) To what extent did participants attain their stated course goals? (3) To what extent did career coaching contribute to participants' current job situation? Analysis of quantitative and qualitative survey responses indicated that participants consistently reported increased levels of confidence after career coaching in terms of their ability to identify appropriate job positions, pursue job opportunities, and reflect on their own development and their overall career readiness. Most participants also reported that they had met their goals and valued their career‐coaching experience. At the time of the survey, five of the participants reported that they had found jobs within the field.